Total and Regional White Matter Lesions Are Correlated With Motor and Cognitive Impairments in Carriers of the FMR1 Premutation - Hocking, Darren R.; Loesch, Danuta Z.; Trost, Nicholas; Bui, Minh Q.; Hammersley, Eleanor; Francis, David; Tassone, Flora; Storey, Elsdon (Frontiers in Neurology, 2019)
This study explores the relationships between hemispheric and cerebellar white matter lesions and motor and cognitive impairments in male carriers of Fragile-X Mental Retardation 1 (FMR1) premutation alleles, and in a subgroup of these carriers affected with Fragile X-Associated Tremor/Ataxia syndrome (FXTAS). Regional and total white matter hyperintensities (wmhs) on MRI, assessed using semiquantitative scores, were correlated with three motor rating scales (ICARS, UPDRS, Tremor), and neuropsychological measures of nonverbal reasoning, working memory and processing speed, in a sample of 30 male premutation carriers aged 39-81 years, and separately in a subsample of 17 of these carriers affected with FXTAS. There were significant relationships between wmhs in the infratentorial region and all three motor scales, as well as several cognitive measures - Prorated IQ, Matrix Reasoning, Similarities, and the Symbol Digit Modalities Test, in the total sample of carriers, as well as in the FXTAS group separately. This shows that whms within the infratentorial region show correlations across the categories of clinical status for a range of motor and cognitive impairments. In the FXTAS group, there was a highly significant relationship between supratentorial (periventricular) lesions and parkinsonism, and between both periventricular and supratentorial deep white matter and ICARS ataxia score. These findings further support the relevance of white matter changes in different brain regions to the motor and cognitive deficits across the spectrum of premutation involvement. Future longitudinal studies using larger sample sizes will be necessary to examine the factors that lead to conversion to a greater extent of neurological involvement as seen in the progression across the FXTAS spectrum.